Freedom and Neurobiology: A Scotistic Account - Labooy, Guus (Zygon, 2004)
With the aid of some Scotistic conceptual distinctions, I develop a way of meeting the apparent deterministic sway of neurobiology. I make a careful distinction between formal and material freedom. Formal freedom, the ability to will or not to will a certain state of affairs regardless of whether it can be effectuated, remains, even if our material freedom to effectuate it is hampered by neurobiological mechanisms. These conceptual findings are linked with contemporary empirical research on obsessive-compulsive disorder and the possibility of volitional modulation of cerebral function.